The Effect of Probing – Prompting Technique on Reading Achievement - Rizqi Nadia Putri; Taufiqulloh Taufiqulloh; Endang Sulistianingsih (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
The fact that most of the students in Junior High School are lack of vocabulary, lazy in reading a long text and low motivation in reading textbooks can be solved by choosing an appropriate method in teaching reading. The aimed of this research was to find out whether the probing-prompting technique was effective for the students' reading achievement. The word “Probing” means research and explore, meanwhile “prompting” means push and guide. In probing-prompting, students are required to answer the question by their own words or sentences. Two groups design was applied, and the participants were eighth students of Junior High School in Tegal. We used reading testing in collecting the data, pre and post-test were conducted. And the data analysis calculated using SPSS program. Based on data analysis using an independent sample t-test, it was revealed that the t-test was higher than t-table (4.332>1.672). We state a conclusion; the use of probing prompting technique is effective because students who taught using probing-prompting technique perform better achievement on reading.